2011
DOI: 10.1016/j.envexpbot.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Transport of DMAA and MMAA into rice (Oryza sativa L.) roots

Abstract: (As(V)) transport into plant cells has been well studied. A study on rice (Oryza sativa L.) showed that arsenite is transported across the plasma membrane via glycerol transporting channels. Previous studies reported that the dimethylarsinic acid (DMAA) and monomethylarsonic acid (MMAA) uptake in duckweed (Spirodela polyrhiza L.) differed from that of As(V), and was unaffected by phosphate (H 2 PO 4 ). This article reports the transport mechanisms of DMAA and MMAA in rice roots. Linear regression analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…2B). This might be due to the fact that DMA is transported through aquaglyceroporin (Rahman et al, 2010 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). This might be due to the fact that DMA is transported through aquaglyceroporin (Rahman et al, 2010 …”
Section: Discussionmentioning
confidence: 99%
“…This might be because DMA uptake in rice roots is independent of Fe 2+ concentrations in growing medium (Rahman et al, 2011), and can be explained by its uptake mechanisms in plants. Kinetic studies of DMA influx in rice roots showed that the glycerol transporter (aquaglyceroporin) in root plasma membrane favors DMA uptake (Rahman et al, 2010), and rice aquaporin Lsi1 is also supposed to mediate the uptake of un-dissociated pentavalent DMA (Li et al, 2009). In addition, Fe-hydroxide on plant root surfaces does not favour DMA adsorption (Rahman et al, 2008a;Rahman et al, 2008b).…”
Section: Effect Of Excess Fe +2 On Dma Uptake In Rice Rootsmentioning
confidence: 99%
“…Li et al ( 2009 ) discovered that the silicon transporter Lsi1 (aquaporin, NIP 1;2), which is known to be involved in arsenite uptake, can also mediate the uptake of undissociated methylated As in rice. It has also been found that MMA and DMA were taken up into rice roots via the same pathway as glycerol, i.e., through aquaporins, as increased glycerol concentrations significantly inhibited their uptake (Rahman et al, 2011 ). Even though little is known about the solution chemistry of TMSb, it thus seems possible that TMSb was taken up via an aquaporin family based transporter in a similar manner to As(III) and Sb(III).…”
Section: Discussionmentioning
confidence: 99%
“…This problem becomes serious concern because once arsenic is released in the soil and water resources, it is bioaccumulated by the terrestrial and aquatic biota, and subsequently enters in the human or animal food chain [5,6]. In highly arsenic contaminated (≥0.01 mg L −1 ) area, the migration of arsenic from soil to water and plant is a serious problem, becoming a major threat to sustainable agriculture practices and food security [7,8]. Empirical data shows that the Arsenic concentration of arsenic in contaminated soils lies between 10 mg kg −1 and as high as 30,000 mg/kg [9].…”
Section: Introductionmentioning
confidence: 99%